Davos 1995 Review
A review of the annual meeting of the World Economic Forum that took place in Davos, Switzerland in 1995. The highlights include interviews with Boutros Boutros-Ghali, Pierre Salinger, Sir Shridath Ramphal, Ingvar Carlsson, George Soros, Jaime Alatorre, Jean-Luc Dehaene, Sir Charles Powell, Peter Norman, Sir Samuel Brittan, Will Hutton, Carlo de Benedetti, Carl Hahn, Dieter Pommerening, Herbert Worner, Sir Michael Perry, Fan Gang, Tansu Çiller, Nabil Shaath, Anders Aslund, Vadim Biryukov, George Mallinckrodt, Percy Barnevik, Tatsura Toyoda, and Alexander Trotman.